Low-Density Lipoprotein Receptor Deficiency Attenuates Neuroinflammation through the Induction of Apolipoprotein E - Mailleux, Jo; Timmermans, Silke; Nelissen, Katherine; Vanmol, Jasmine; Vanmierlo, Tim; van Horssen, Jack; Bogie, Jeroen F. J.; Hendriks, Jerome J. A. (Frontiers in Immunology, 2017)
Objective: We aimed to determine the role of the low-density lipoprotein receptor (LDLr) in neuroinflammation by inducing experimental autoimmune encephalomyelitis (EAE) in ldlr knock out mice. Methods: MOG35-55 induced EAE in male and female ldlr-/- mice was assessed clinically and histopathologically. Expression of inflammatory mediators and apolipoprotein E (apoE) was investigated by qPCR. Changes in protein levels of apoE and tumor necrosis factor alpha (TNF) were validated by western blot and ELISA respectively. Results: Ldlr-/- attenuated EAE disease severity in female, but not in male EAE mice, marked by a reduced proinflammatory cytokine production in the central nervous system (CNS) of female ldlr-/- mice. Macrophages from female ldlr-/- mice showed a similar decrease in proinflammatory mediators, an impaired capacity to phagocytose myelin and enhanced secretion of the anti-inflammatory apoE. Interestingly, apoE/ldlr double knock out abrogated the beneficial effect of ldlr depletion in EAE. Conclusion: Collectively, we show that ldlr-/- reduces EAE disease severity in female but not in male EAE mice, and that this can be explained by increased levels of apoE in female ldlr-/- mice. Although the reason for the observed sexual dimorphism remains unclear, our findings show that LDLr and associated apoE levels are involved in neuroinflammatory processes.